Colonisation of toxic environments drives predictable life‐history evolution in livebearing fishes (Poeciliidae). (4th November 2013) - Riesch, Rüdiger; Plath, Martin; Schlupp, Ingo; Tobler, Michael; Brian Langerhans, R.; Gaillard, Jean‐Michel
Abstract New World livebearing fishes (family Poeciliidae) have repeatedly colonised toxic, hydrogen sulphide‐rich waters across their natural distribution. Physiological considerations and life‐history theory predict that these adverse conditions should favour the evolution of larger offspring. Here, we examined nine poeciliid species that independently colonised toxic environments, and show that these fishes have indeed repeatedly evolved much larger offspring size at birth in sulphidic waters, thus uncovering a widespread pattern of predictable evolution. However, a second pattern, only indirectly predicted by theory, proved additionally common: a reduction in the number of offspring carried per clutch (i.e. lower fecundity). Our analyses reveal that this secondary pattern represents a mere consequence of a classic life‐history trade‐off combined with strong selection on offspring size alone. With such strong natural selection in extreme environments, extremophile organisms may commonly exhibit multivariate phenotypic shifts even though not all diverging traits necessarily represent adaptations to the extreme conditions.